Evaluating the potential cost-effectiveness of microarray patches to expand access to hepatitis B birth dose vaccination in low-and middle-income countries: A modelling study. - Christopher P Seaman; Mercy Mvundura; Collrane Frivold; Christopher Morgan; Courtney Jarrahian; Jess Howell; Margaret Hellard; Nick Scott (Public Library of Science (PLoS), 2022)
Timely birth dose vaccination is key for achieving elimination of hepatitis B, however, programmatic requirements for delivering current vaccine presentations to births outside of health facilities inhibits coverage within many low-and middle-income countries (LMICs). Vaccine technologies in development such as microarray patches (MAPs) could assist in overcoming these barriers, but procurement could incur higher per-dose commodity costs than current ten-dose (US$0.34) and single-dose (US$0.62) vial presentations, necessitating an evaluation of the economic value proposition for MAPs. Within 80 LMICs offering universal hepatitis B birth dose vaccination, the cost-effectiveness of using MAPs to expand coverage was evaluated using a mathematical model. We considered three potential per dose MAP prices (US$1.65, US$3.30, and US$5.00), and two potential MAP use-cases: (1) MAPs are used by lay-health workers to expand birth dose coverage outside of health facility settings, and (2) MAPs are also preferred by qualified health workers, replacing a proportion of existing coverage from vaccine vials. Analysis took the health system perspective, was costed in 2020 US$, and discounted at 3% annually. Across minimal (1% additional coverage) and maximal (10% additional and 10% replacement coverage) MAP usage scenarios, between 2.5 (interquartile range [IQR]: 1.9, 3.1) and 38 (IQR: 28,44) thousand DALYs were averted over the estimated 2020 birth cohort lifetime in 80 LMICs. Efficiency of MAPs was greatest when used to provide additional coverage (scenario 1), on average saving US$88.65 ($15.44, $171.22) per DALY averted at a price of US$5.00 per MAP. Efficiency was reduced when used to replace existing coverage (scenario 2); however, at prices up to US$5.00 per MAP, we estimate this use-case could remain cost-effective in at least 73 (91%) modelled LMICs. Our findings suggest even at higher procurement costs, MAPs are likely to represent a highly cost-effective or cost-saving mechanism to expand reach of birth dose vaccination in LMICs.